Models of self in families of people with spina bifida - FREIRE, Viviam Rafaela Barbosa Pinheiro (Universidade Federal do Pará, 2019)
Models of self reveal cultural views regarding the competences that children should acquire, and these views tend to be shared by people within the same environment. Thus, this study aims to evaluate the models of self in families of people with spina bifida. Seventeen caregivers answered an online questionnaire containing socio-demographic questions and three scales of self: autonomous, related and autonomous-related. The data were analyzed using descriptive statistics and techniques of multivariate analysis. The main results indicate that the most valued model of self was the autonomous-related model, reflecting the desire that children develop autonomy as well as interpersonal relationships. Such a model, however, is distinct from that of family groups of people with typical development living in the same cultural environment, indicating the need for families of people with spina bifida to receive support to reach their developmental goals.